Simplified mechanistic model for the separation of dispersed oil-water horizontal pipe flows - Evripidou, Nikola; Voulgaropoulos, Victor; Angeli, Panagiota (My University, 2019)
A mechanistic model that predicts the separation of oil-water dispersed horizontal pipe flows was investigated. Different droplet diameter averages were implemented in the model and the accuracy of the resulting predictions was assessed by comparing each case against experimental data. The experimental data used was obtained in a pilot scale two-phase flow facility using tap water and oil (828 kg m-3, 5.5 mPa s) as test fluids. The results show that the separation length is highly sensitive to the drop diameter, but further investigation is required to determine which drop diameter average produces more accurate predictions of the flow profile.